Sustainable development of rural aboriginal communities of northern British Columbia: a case study of the Tl'azt'en nation - Baruah, Bipasha (Author); Wilkerson, Orland (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 1998)
This study investigates and identifies major factors that impede or facilitates the sustainable development of rural First Nations communities of northern British Columbia, through a case study of the Tl'azt'en Nation. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1195907